CULTURAL AND PHILOSOPHICAL INSIGHTS INTO CHINESE ACCULTURATION IN JAVANESE BATIK: COASTAL TO HINTERLAND TRANSITIONS - Rahayuningtyas, Putrie; Andarwulan, Trisna; Endrayanto, Nanang (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
This research examines the philosophical meanings of motifs and colors in Javanese batik that has undergone acculturation with Chinese culture from coastal to inland areas. The research focuses on batik from Pekalongan, Lasem, as well as Demak and Kudus. Using a qualitative approach and discourse analysis, this study reveals how batik motifs and colors reflect the fusion of Javanese and Chinese cultural values. The results show that acculturation is reflected in motifs such as hong birds (phoenix), dragons, butterflies, and chrysanthemums in coastal batik, while in inland areas it is seen in Sudagaran batik. In terms of color, Chinese influence is evident in the use of getih pitik red (chicken blood), beer bottle green, and dark blue in Lasem batik, as well as bright color combinations such as red, yellow, and green in Pekalongan batik. The philosophical meanings in these motifs and colors represent values of luck, prosperity, balance, and harmony believed in Chinese culture, while adapting to Javanese aesthetic values.